Bridging Public Trust and Banking Behavior: Local Government Leaders as Key Opinion Leaders in Regional Bank Marketing Strategies - Fauzy, Shanty Dewi; Kholil, Kholil; Lestari, Puji; Alifahmi, Hifni (Baileo: Jurnal Sosial Humaniora, 2025)
This study examines the role of local governments as Key Opinion Leaders (KOLs) in the marketing communication strategies of PT. Bank Nagari, a Regional Development Bank (RDB) in West Sumatra. The research problem addresses the low saving intention of the public amid intense national banking competition, the dominance of digital banks, and limited financial literacy. Using a qualitative expertise-based research design, data were collected through semi-structured in-depth interviews with local government officials, Bank Nagari executives, and academics, complemented by secondary sources from financial authorities and statistical agencies. Data were analyzed using Creswell’s six-step approach supported by MaxQDA, with validity ensured through source triangulation. Findings indicate that local governments effectively function as KOLs, enhancing Bank Nagari’s image, credibility, and public trust. The personal credibility of regional leaders significantly influences saving intention, though its effectiveness remains limited by narrow segmentation and underutilized digital marketing. Cross-actor collaboration—including local governments, media, community groups, and academics—strengthens brand image and broadens audience reach. Theoretically, the study proposes an Integrated Marketing Communication (IMC) model that integrates the Two-Step Flow Theory, Heart Communication Theory, and the VisCAP Model. Its novelty lies in shifting the KOL focus from celebrities or digital influencers to government actors, highlighting the transfer of public trust into productive economic behavior. Practically, the study recommends strengthening local value-based campaigns, digital engagement, and market expansion to reinforce regional banking competitiveness.